A Psychoeducational CBT-based Group Intervention ("Drop It") for Repetitive Negative Thinking: Theoretical Concepts and Treatment Processes. Issue 3 (3rd July 2022) - Rogiers, Roland; Baeken, Chris; Watkins, Edward R.; van den Abbeele, Dirk; Remue, Jonathan; de Raedt, Rudi; Lemmens, Gilbert M.D.
ABSTRACT: Repetitive negative thinking (RNT)—such as worry and rumination—is an important transdiagnostic factor in the onset, course, and recurrence of depressive and anxiety disorders. This article describes a psychoeducational cognitive behavioral therapy (CBT)-based group intervention entitled "Drop It" that focuses exclusively on treating RNT in patients with major depressive disorder and/or generalized anxiety disorder. The theoretical concepts and treatment goals of the intervention are outlined. The organization and therapeutic processes of the different sessions are described and illustrated with statements of participants. Special attention is given to how the intervention capitalizes on the group structure and process to maximize the effectiveness of psychoeducation and CBT-based techniques. We also provide practical guidelines for clinicians treating patients with RNT.